Liver Transplantation for Hepatocellular Carcinoma: A Single Center Resume Overlooking Four Decades of Experience - Nikos Emmanouilidis; Rickmer Peters; Bastian P. Ringe; Zeynep Güner; Wolf Ramackers; Hüseyin Bektas; Frank Lehner; Michael Manns; Jürgen Klempnauer; Harald Schrem (Journal of Transplantation)
Background. This is a single center oncological resume overlooking four decades of experience with liver transplantation (LT) for hepatocellular carcinoma (HCC). Methods. All 319 LT for HCC that were performed between 1975 and 2011 were included. Predictors for HCC recurrence (HCCR) and survival were identified by Cox regression, Kaplan-Meier analysis, Log Rank, and χ2-tests where appropriate. Results. HCCR was the single strongest hazard for survival (exp⁡B=10.156). Hazards for HCCR were tumor staging beyond the histologic MILAN (exp⁡B=3.645), bilateral tumor spreading (exp⁡B=14.505), tumor grading beyond G2 (exp⁡B=8.668), and vascular infiltration of small or large vessels (exp⁡B=11.612, exp⁡B=18.324, resp.). Grading beyond G2 (exp⁡B=10.498) as well as small and large vascular infiltrations (exp⁡B=13.337, exp⁡B=16.737, resp.) was associated with higher hazard ratios for long-term survival as compared to liver transplantation beyond histological MILAN (exp⁡B=4.533). Tumor dedifferentiation significantly correlated with vascular infiltration (χ2p=0.006) and intrahepatic tumor spreading (χ2p=0.016). Conclusion. LT enables survival from HCC. HCC dedifferentiation is associated with vascular infiltration and intrahepatic tumor spreading and is a strong hazard for HCCR and survival. Pretransplant tumor staging should include grading by biopsy, because grading is a reliable and easily accessible predictor of HCCR and survival. Detection of dedifferentiation should speed up the allocation process.